The insulin-like peptides Dilp2 and Dilp6 exhibit divergent responses to dietary sugar and protein in Drosophila larvae - Miyuki Suzawa; W. Kyle McPherson; Kelly E. Dunham; Elizabeth E. Van Gorder; Shivani Reddy; Leila A. Jamali; Michelle L. Bland (Proceedings of the National Academy of Sciences, 2025)
Nutrient intake drives secretion of insulin and insulin-like peptides that stimulate anabolic metabolism and tissue growth. Eight Drosophila insulin-like peptides (Dilps) are encoded in the Drosophila genome; whether these Dilps respond uniformly to changes in dietary nutrients is unknown. Here, we investigate the endocrine responses of Dilp2, secreted by brain insulin-producing cells, and Dilp6, produced by the fat body, to dietary sugar and protein in mid-third instar Drosophila larvae. Starvation leads to a profound reduction in circulating Dilp2 without affecting circulating Dilp6 levels. Diets containing sugar alone drive nutrient storage and increase hemolymph Dilp6, but do not promote Dilp2 release. In contrast, dietary protein drives growth and restores hemolymph Dilp2 but strongly reduces circulating Dilp6. Furthermore, circulating levels of Dilp2 and Dilp6 are modulated by the ratio of sugar to protein in the diet. We find that depleting circulating Dilp6 via fat body specific knockdown or increasing insulin receptor (InR) levels in fat body leads to increased levels of triglyceride storage but decreased peripheral growth. Our results suggest that Dilp6, a hormone produced in response to dietary sugar, may direct the use of sugar for growth instead of fat storage at the end stage of larval development. Our findings reveal different modes of regulation for Dilp2 and Dilp6 and raise the question of how the single known Drosophila InR integrates divergent signals from distinct Dilps to control growth and metabolism.